Penalty for breach of responsibility for negotiations in government contracts: Comparative Study - جعفر, رشا محمد; خلف, سهى محمد (Journal of Legal Sciences, 2021)
Negotiations in administrative contracts represent an important preparatory stage in which discussions and discussions between the administrative authority and the party wishing to contract with them will be held on one of the issues related to the contract to be concluded whereby the different views of the parties of the contractual relationship are brought together to exchange or achieve common interests.The importance  of negotiations in administrative contracts and their significant and effective role in protecting state funds. The inadequacy of Iraqi legislation in the development of an integrated legal framework for this important phase, and the many problems that appear in this stage before the conclusion of the contract , Furthermore, the procedures between management and individuals during the negotiation phase do not in themselves create any contractual obligations, taking into account liability arising from damages that may be caused to one party by a fault of the other party .We dealt with the subject of our research according to a plan comprising an introduction, three chapters and ending with a conclusion.